Analisis Efektivitas Aplikasi Digital Banking Byond By Bsi Terhadap Kepuasan Nasabah Bank Syariah Indonesia di Kabupaten Pekalongan - Pradipta Febiyanto; Muhammad Shofiyuddin (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
The purpose of this study is to evaluate how well the Byond by BSI digital application affects Pekalongan Regency customers' satisfaction. Efficiency, realibility, fulfillment, privacy, responsiveness, remuneration, and contract are the independent variables that were used in this study. The happiness of customers is the dependent variable. Customers who have utilized the Byond by BSI digital banking application at Bank Syariah Indonesia KCP Pekalongan Ambokembang make up the study's population. The Slovin formula is used in this study's sample, which consists of 90 clients with a 10% error rate. Multiple regression analysis is one method for looking at how independent and dependent variables relate to one another. Multiple regression analysis is one method for looking at how independent and dependent variables relate to one another. This survey indicates that BSI digital banking apps greatly increase customer satisfaction in the following areas: contact, efficiency, dependability, fulfillment, data protection, responsiveness, and compensation.